Some remarks on additive arithmetical functions - Kátai, I. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Катай. Некоторые замечания к аддитивным арифметическим функциямI. Katajus. Pastabos apie adityvines aritmetines funkcijas